Qualidade da água e de sedimentos nos reservatórios das usinas hidrelétricas de Nova Ponte e Miranda Minas Gerais - Flauzino, Fabrício Silvério (2014)
This work has the objective of evaluating the quality of water and sediments in the reservoirs of hydroelectric plants of Nova Ponte and Miranda, in Minas Gerais State - Brazil. The collection of water samples and sediments were carried out in two distinct seasons: Dried (March) and rainy (September) of the year 2013 results of physico-chemical analyzes of the water showed values above the established limits by law, for the following parameters: Dissolved Oxygen, Total Dissolved Solids, Total Suspended Solids and sedimentable solids, and sediment samples: Total Cadmium, Total Lead, Total Copper, Nickel and Zinc Total Total. The values of the tests of water samples were interpreted according to the limits of acceptance for each individual substance in each class, aimed at meeting the water quality standards established by Resolução No. 357 of the CONAMA (2005). We compared the results of tests on samples of sediment to the levels of acceptance of Resolution No. 454 of the CONAMA (2012). To help understand the results of physico-chemical and bacteriological analyzes of water and physical and chemical characteristics of sediments in the study area was mapped on the use and occupation of land. This mapping has identified the presence of 58% of the anthropic use, 40% of natural vegetation cover and 2% occupied by water bodies. Classification of Water Quality Index (AQI) shows that the sampling points, mostly fluctuate between excellent and good, and the Trophic State Index (TSI) was the predominant mesotrophic. The evaluation of physical, chemical and biological variables of the water, and physical and chemical characteristics of sediments from the lakes of Nova Ponte and Miranda, coupled with GIS techniques, provided better knowledge of the environmental conditions of the study area, and the results obtained can be used as primary data sources to promote local and regional planning and environmental management.